Preparation method of hierarchical polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material
By forming a hierarchical structure of polypyrrole/NiCoAl-LDH electrode material on cotton fibers, the problem of poor conductivity of cotton fibers is solved, and the performance and service life of the electrode material are significantly improved. It is suitable for wearable electronic devices.
Patent Information
- Application Number
- CN202211523880.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-01
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-12-01
AI Technical Summary
The prior art is difficult to impart conductive and capacitive properties to cotton fibers, resulting in a shortening of the service life of flexible supercapacitor electrode materials.
By growing ZIF-67 in situ as a self-sacrifice template on cotton fibers, NiCoAl-LDH nanoarrays are derived and chemically oxidized polymerized thereon to form a hierarchical polypyrrole/NiCoAl-LDH/cotton fiber electrode material.
It significantly improves the conductivity, specific capacitance and cycling stability of the electrode material, extends the service life of the electrode material, and improves its applicability in wearable electronic devices.
Smart Images

Figure CN115787300B_ABST
Abstract
Description
Technical field:
[0001] The invention belongs to the field of flexible electronic technology and relates to a method for preparing a flexible supercapacitor electrode material, in particular to a method for preparing a hierarchical polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material. Background technology:
[0002] Wearable electronic products are gradually entering people's daily lives. Traditional rigid energy storage devices can no longer meet the energy storage needs of flexible wearable electronic devices. Flexible supercapacitors are well suited for wearable electronic devices due to their high energy storage capacity, good safety, and resistance to bending. Electrode materials are the main components of supercapacitors, and the development of high-performance flexible electrode materials is imperative.
[0003] Fiber-based flexible electrode materials are lightweight, bendable, and can be integrated on a large scale, which can better realize the wearability of flexible energy storage devices. Cotton fiber has excellent flexibility and high mechanical flexibility, making it one of the ideal substrates for preparing flexible supercapacitor electrode materials. However, cotton fiber is an insulating material, so how to give it conductive and capacitive properties becomes a key issue.
[0004] Polypyrrole is a conductive polymer with high conductivity and capacitance performance, and good compatibility with the substrate. It can be combined with cotton fiber to prepare flexible electrode materials. However, polypyrrole expands and contracts in volume during repeated charge and discharge, which makes the molecular chain easy to dedope, thus losing electrochemical activity, which seriously shortens the service life of the electrode material.
[0005] Three-dimensional double hydroxides (LDHs) derived from metal organic frameworks (MOFs) as templates are a new type of electrode material with adjustable morphology and structure and high specific capacitance. Through reasonable design, it can form core-shell, hollow framework, microsphere and other structures with high specific surface area and rich pores, thereby improving the stability and electrochemical performance of electrode materials. Researchers compounded conductive polymers with three-dimensional LDHs with excellent stability to effectively prevent dedoping of conductive polymers [Yu J, Yao D, Wu ZD, et al. ACS Appl. Energy Mater, 2021, 4: 3093-3100.]. However, in these studies, electrode materials were prepared only by coating and printing active materials on flexible substrates such as nickel foam and carbon fiber cloth. During use, active materials are prone to aggregation and weak bonding to the substrate. Summary of the invention:
[0006] The purpose of the present invention is to provide a method for preparing a hierarchical polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material, which overcomes the problem of how to give cotton fibers conductive and capacitive properties in the prior art. The present invention gives cotton fibers good conductivity, specific capacitance, and cycle stability.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing a hierarchical polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material, characterized by comprising the following steps:
[0009] Firstly, a cobalt-based metal-organic framework (ZIF-67) was in situ grown on a biomass cotton fiber substrate, and then it was used as a self-sacrificial template to derive a nickel cobalt aluminum hydroxide (NiCoAl-LDH) nanoarray by introducing nickel nitrate hexahydrate and aluminum nitrate nonahydrate. Furthermore, pyrrole was introduced as a raw material and FeCl3·6H2O as an oxidant to carry out chemical oxidation polymerization on the NiCoAl-LDH / cotton fiber, and polypyrrole was grown on the NiCoAl-LDH nanoarray to form a hierarchical structure, thus obtaining a polypyrrole / NiCoAl-LDH / cotton fiber electrode material.
[0010] The above method comprises the following steps:
[0011] Step 1: (ZIF-67) n / Preparation of cotton fiber:
[0012] Cobalt nitrate hexahydrate and 2-methylimidazole were dissolved in methanol solution respectively, cotton fiber was immersed in the methanol solution of 2-methylimidazole, and the methanol solution of cobalt nitrate hexahydrate was slowly added thereto, and aged at room temperature. After taking out the cotton fiber, it was washed with deionized water and dried to obtain ZIF-67 / cotton fiber; by repeating the above steps, different ZIF-67 loading amounts (ZIF-67) were obtained. n / cotton fiber;
[0013] Step 2: Preparation of NiCoAl-LDH / cotton fiber:
[0014] (ZIF-67) n / cotton fiber is immersed in an ethanol-water mixed solution of nickel nitrate hexahydrate and aluminum nitrate nonahydrate, placed in a reactor, and subjected to hydrothermal reaction. After the reaction is completed, the cotton fiber is cooled to room temperature, and the cotton fiber is taken out and dried to obtain NiCoAl-LDH / cotton fiber;
[0015] Step 3: Preparation of polypyrrole / NiCoAl-LDH / cotton fiber:
[0016] Pyrrole was dissolved in deionized water, NiCoAl-LDH / cotton fiber was placed in the solution, and magnetic stirring was performed in an ice-water bath; ferric chloride hexahydrate was dissolved in deionized water, and added dropwise to the pyrrole monomer solution, and reacted for a period of time at room temperature. After the cotton fiber was taken out, it was washed with hydrochloric acid and deionized water, and dried to obtain a polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material.
[0017] The above method comprises the following steps:
[0018] Step 1: (ZIF-67) n / Preparation of cotton fiber:
[0019] Cobalt nitrate hexahydrate and 2-methylimidazole were dissolved in methanol solution, respectively, cotton fibers of 10 cm × 10 cm were immersed in the methanol solution of 2-methylimidazole, and the methanol solution of cobalt nitrate hexahydrate was slowly added thereto, and aged at room temperature for 24 h. The cotton fibers were taken out and washed with deionized water for 2 to 3 times, and dried to obtain ZIF-67 / cotton fibers. By repeating the above steps, (ZIF-67) with different ZIF-67 loading amounts were obtained. n / cotton fiber;
[0020] Step 2: Preparation of NiCoAl-LDH / cotton fiber:
[0021] (ZIF-67) n / cotton fiber is immersed in an ethanol-water mixed solution of nickel nitrate hexahydrate and aluminum nitrate nonahydrate, placed in a reactor, and subjected to hydrothermal reaction at 90°C for 1 hour. After the reaction is completed, the cotton fiber is cooled to room temperature, and the cotton fiber is taken out and dried to obtain NiCoAl-LDH / cotton fiber;
[0022] Step 3: Preparation of polypyrrole / NiCoAl-LDH / cotton fiber:
[0023] Pyrrole was dissolved in deionized water, NiCoAl-LDH / cotton fiber was placed in the solution, and magnetic stirring was performed in an ice-water bath for 30 minutes; a certain amount of ferric chloride hexahydrate was dissolved in deionized water, and was dropwise added into the pyrrole monomer solution within 30 minutes. The mixture was reacted for a period of time at room temperature, and the cotton fiber was taken out, washed with hydrochloric acid and deionized water, and dried to obtain a polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material.
[0024] The above method comprises the following steps:
[0025] Step 1: Preparation of (ZIF-67)5 / cotton fiber:
[0026] 3.87 g of cobalt nitrate hexahydrate and 4 g of 2-methylimidazole were dissolved in 120 mL of methanol solution, and cotton fibers of 10 cm × 10 cm were soaked in the methanol solution of 2-methylimidazole, and the methanol solution of cobalt nitrate hexahydrate was slowly added thereto, and aged at room temperature for 24 h. The cotton fibers were taken out and washed with deionized water, and dried at 50 °C to obtain ZIF-67 / cotton fibers; the above steps were repeated 4 times to obtain different (ZIF-67)4 / cotton fibers;
[0027] Step 2: Preparation of NiCoAl-LDH / cotton fiber:
[0028] Nickel nitrate hexahydrate and aluminum nitrate nonahydrate in a molar ratio of 0.5 to 4:1 were dissolved in 60 mL of an ethanol-water mixed solution, (ZIF-67)4 / cotton fiber was placed in the mixed solution, and hydrothermally reacted at 90°C for 1 h. After the reaction was completed, the cotton fiber was cooled to room temperature, washed with deionized water, and dried at 60°C to obtain NiCoAl-LDH / cotton fiber;
[0029] Step 3: Preparation of polypyrrole / NiCoAl-LDH / cotton fiber:
[0030] 0.2M pyrrole was dissolved in deionized water, NiCoAl-LDH / cotton fiber was placed in the solution, and magnetic stirring was performed in an ice-water bath for 30 minutes; ferric chloride hexahydrate with a molar ratio of 4 times that of pyrrole was dissolved in deionized water, and added dropwise to the pyrrole monomer solution within 30 minutes, and reacted for 120 minutes under ice-water bath conditions. After the cotton fiber was taken out, it was washed with hydrochloric acid and deionized water, and dried at 60°C to obtain a polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material.
[0031] Compared with the prior art, the present invention has the following advantages and effects:
[0032] The hierarchical structure polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material prepared by the present invention uses cotton fiber as a flexible substrate, and uses ZIF-67 as a self-sacrificial template on its surface to derive a NiCoAl-LDH array, which increases the reactive area of the electrode material and has a multi-metal synergistic effect, significantly improving the electrochemical performance; the metal ions in LDHs form coordination bonds with -OH on the cotton fiber, thereby enhancing the bonding strength between the active material and the cotton fiber substrate; the hierarchical structure constructed by polypyrrole and NiCoAl-LDH array provides a rich space for the phase change of the polypyrrole molecular chain, preventing it from being dedoped during repeated charge and discharge, and significantly improving the structural stability and electrochemical performance of the electrode material. The polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material exhibits excellent electrochemical energy storage performance (5mAcm -2 1744.79mFcm -2), good cycle stability (1000 times, 80.95%), physical and mechanical properties and wearability. Description of the drawings:
[0033] Figure 1 GCD curves of polypyrrole / NiCoAl-LDH / cotton fiber electrode materials at different current densities of the present invention;
[0034] Figure 2 This is the cycle stability curve of the polypyrrole / NiCoAl-LDH / cotton fiber electrode material after 1000 charge and discharge cycles. Specific implementation method:
[0035] The present invention is described in detail below in conjunction with specific embodiments. These embodiments are used to illustrate the present invention but are not limited to the scope of the present invention. The implementation conditions adopted in the embodiments can be further adjusted according to the specific experimental environment, and the implementation conditions not indicated are usually the conditions in conventional experiments.
[0036] The present invention proposes to design and construct a hierarchical structure electrode material using conductive polypyrrole and NiCoAl-LDH with high capacitance characteristics on the surface of cotton fiber. The metal ions in LDHs are coordinated with -OH on the cotton fiber to enhance the bonding strength between the NiCoAl-LDH array and the cotton fiber substrate, thereby improving the stability of the electrode material; the uniform pore structure of the NiCoAl-LDH array provides phase change space for polypyrrole, thereby extending the service life of the electrode material. Finally, a flexible wearable supercapacitor electrode material with excellent capacitance performance and long service life is obtained, providing a new idea for the high-value utilization of cotton fibers.
[0037] The preparation method of the hierarchical structure polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material of the present invention is achieved by the following steps:
[0038] (1)(ZIF-67) n / Preparation of cotton fiber:
[0039] 3.87 g of cobalt nitrate hexahydrate and 4 g of 2-methylimidazole were dissolved in 120 mL of methanol solution, and cotton fibers of 10 cm × 10 cm were immersed in the methanol solution of 2-methylimidazole. The methanol solution of cobalt nitrate hexahydrate was slowly added thereto, and the fibers were aged at room temperature for 24 h. The cotton fibers were taken out and washed with deionized water, and dried at 50 °C to obtain ZIF-67 / cotton fibers. The above steps were repeated 1, 2, 3, 4, and 5 times to obtain (ZIF-67) with different ZIF-67 loadings. n / cotton fiber.
[0040] (2) Preparation of NiCoAl-LDH / cotton fiber:
[0041] Nickel nitrate hexahydrate and aluminum nitrate nonahydrate with molar ratios of 0.5:1, 1:1, 2:1, 3:1, and 4:1 were dissolved in 60 mL of ethanol-water mixed solution. n / cotton fiber was placed in the mixed solution and subjected to hydrothermal reaction at 90°C for 1 h. After the reaction was completed, it was cooled to room temperature, and the cotton fiber was taken out, washed with deionized water, and dried at 60°C to obtain NiCoAl-LDH / cotton fiber.
[0042] (3) Preparation of polypyrrole / NiCoAl-LDH / cotton fiber:
[0043] 0.2M pyrrole was dissolved in deionized water, NiCoAl-LDH / cotton fiber was placed in the solution, and magnetic stirring was performed for 30 minutes in an ice-water bath; ferric chloride hexahydrate with a molar ratio of 1, 2, 3, 4, and 5 times that of pyrrole was dissolved in deionized water, and added dropwise to the pyrrole monomer solution within 30 minutes, and reacted for 30, 60, 90, 120, and 150 minutes under ice-water bath conditions. After the cotton fiber was taken out, it was washed with hydrochloric acid and deionized water, and dried at 60°C to obtain polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material.
[0044] Embodiment 1:
[0045] (1) Preparation of (ZIF-67)3 / cotton fiber:
[0046] 3.87 g of cobalt nitrate hexahydrate and 4 g of 2-methylimidazole were dissolved in 120 mL of methanol solution respectively, and cotton fiber of 10 cm × 10 cm size was soaked in the methanol solution of 2-methylimidazole. The methanol solution of cobalt nitrate hexahydrate was slowly added thereto, and aged at room temperature for 24 h. The cotton fiber was taken out and washed with deionized water, and dried at 50 °C to obtain ZIF-67 / cotton fiber; by repeating the above steps 3 times, (ZIF-67)3 / cotton fiber was obtained.
[0047] (2) Preparation of NiCoAl-LDH / cotton fiber:
[0048] Nickel nitrate hexahydrate and aluminum nitrate nonahydrate with a molar ratio of 0.5:1 were dissolved in 60 mL of ethanol-water mixed solution, (ZIF-67)3 / cotton fiber was placed in the mixed solution, and hydrothermally reacted at 90°C for 1 h. After the reaction was completed, it was cooled to room temperature, the cotton fiber was taken out, washed with deionized water, and dried at 60°C to obtain NiCoAl-LDH / cotton fiber.
[0049] (3) Preparation of polypyrrole / NiCoAl-LDH / cotton fiber:
[0050] 0.2M pyrrole was dissolved in deionized water, NiCoAl-LDH / cotton fiber was placed in the solution, and magnetic stirring was performed in an ice-water bath for 30 minutes; ferric chloride hexahydrate with a molar ratio of 1 times that of pyrrole was dissolved in deionized water, and added dropwise to the pyrrole monomer solution within 30 minutes, and reacted for 30 minutes under ice-water bath conditions. After the cotton fiber was taken out, it was washed with hydrochloric acid and deionized water, and dried at 60°C to obtain a polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material.
[0051] Embodiment 2:
[0052] (1) Preparation of (ZIF-67)4 / cotton fiber:
[0053] 3.87 g of cobalt nitrate hexahydrate and 4 g of 2-methylimidazole were dissolved in 120 mL of methanol solution respectively, and cotton fiber of 10 cm × 10 cm size was soaked in the methanol solution of 2-methylimidazole. The methanol solution of cobalt nitrate hexahydrate was slowly added thereto, and aged at room temperature for 24 h. The cotton fiber was taken out and washed with deionized water, and dried at 50 °C to obtain ZIF-67 / cotton fiber; by repeating the above steps 4 times, (ZIF-67)4 / cotton fiber was obtained.
[0054] (2) Preparation of NiCoAl-LDH / cotton fiber:
[0055] Nickel nitrate hexahydrate and aluminum nitrate nonahydrate in a molar ratio of 2:1 were dissolved in 60 mL of ethanol-water mixed solution, (ZIF-67)4 / cotton fiber was placed in the mixed solution, and hydrothermally reacted at 90°C for 1 h. After the reaction was completed, it was cooled to room temperature, and the cotton fiber was taken out, washed with deionized water, and dried at 60°C to obtain NiCoAl-LDH / cotton fiber.
[0056] (3) Preparation of polypyrrole / NiCoAl-LDH / cotton fiber:
[0057] 0.2M pyrrole was dissolved in deionized water, NiCoAl-LDH / cotton fiber was placed in the solution, and magnetic stirring was performed in an ice-water bath for 30 minutes; ferric chloride hexahydrate with a molar ratio of 3 times that of pyrrole was dissolved in deionized water, and added dropwise to the pyrrole monomer solution within 30 minutes, and reacted for 60 minutes under ice-water bath conditions. After the cotton fiber was taken out, it was washed with hydrochloric acid and deionized water, and dried at 60°C to obtain a polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material.
[0058] Embodiment 3:
[0059] (1) Preparation of (ZIF-67)5 / cotton fiber:
[0060] 3.87 g of cobalt nitrate hexahydrate and 4 g of 2-methylimidazole were dissolved in 120 mL of methanol solution respectively, and cotton fibers of 10 cm × 10 cm size were soaked in the methanol solution of 2-methylimidazole. The methanol solution of cobalt nitrate hexahydrate was slowly added thereto, and the fibers were aged at room temperature for 24 h. The cotton fibers were taken out and washed with deionized water, and dried at 50 °C to obtain ZIF-67 / cotton fibers. By repeating the above steps 5 times, different (ZIF-67)5 / cotton fibers were obtained.
[0061] (2) Preparation of NiCoAl-LDH / cotton fiber:
[0062] Nickel nitrate hexahydrate and aluminum nitrate nonahydrate in a molar ratio of 4:1 were dissolved in 60 mL of ethanol-water mixed solution, (ZIF-67)5 / cotton fiber was placed in the mixed solution, and hydrothermally reacted at 90°C for 1 h. After the reaction was completed, it was cooled to room temperature, and the cotton fiber was taken out, washed with deionized water, and dried at 60°C to obtain NiCoAl-LDH / cotton fiber.
[0063] (3) Preparation of polypyrrole / NiCoAl-LDH / cotton fiber:
[0064] 0.2M pyrrole was dissolved in deionized water, NiCoAl-LDH / cotton fiber was placed in the solution, and magnetic stirring was performed in an ice-water bath for 30 minutes; ferric chloride hexahydrate with a molar ratio of 4 times that of pyrrole was dissolved in deionized water, and added dropwise to the pyrrole monomer solution within 30 minutes, and reacted for 90 minutes under ice-water bath conditions. After the cotton fiber was taken out, it was washed with hydrochloric acid and deionized water, and dried at 60°C to obtain a polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material.
[0065] See also Figure 1 , Figure 1 : is the GCD curve of polypyrrole / NiCoAl-LDH / cotton fiber electrode material under different current densities of the present invention. Figure 2 , Figure 2 The cyclic stability curve of the polypyrrole / NiCoAl-LDH / cotton fiber electrode material after 1000 cycles of charge and discharge. The polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material prepared by the present invention exhibits excellent electrochemical energy storage performance (5mA cm -2 1744.79 mF cm -2 ) and good cycle stability (1000 times, 80.95%).
[0066] The above embodiments are only illustrative of the principles and effects of the present invention. A person skilled in the art may make several modifications and improvements without departing from the inventive concept of the present invention, and all of these belong to the protection scope of the present invention.
Claims
1. A method for preparing a hierarchical polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material, characterized in that: The following steps are involved: Firstly, a cobalt-based metal organic framework ZIF-67 was in situ grown on a biomass cotton fiber substrate. Then, it was used as a self-sacrificial template to derive a nickel cobalt aluminum hydroxide NiCoAl-LDH nanoarray by introducing nickel nitrate hexahydrate and aluminum nitrate nonahydrate. Furthermore, pyrrole was introduced as a raw material and FeCl3·6H2O as an oxidant to carry out chemical oxidation polymerization on the NiCoAl-LDH / cotton fiber. Polypyrrole was grown on the NiCoAl-LDH nanoarray to form a hierarchical structure, and the polypyrrole / NiCoAl-LDH / cotton fiber electrode material was obtained.
2. The method for preparing the hierarchical polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material according to claim 1, characterized in that: The following steps are involved: Step 1: (ZIF-67) n / Preparation of cotton fiber: Cobalt nitrate hexahydrate and 2-methylimidazole were dissolved in methanol solution respectively, cotton fiber was immersed in the methanol solution of 2-methylimidazole, and the methanol solution of cobalt nitrate hexahydrate was slowly added thereto, and aged at room temperature. After taking out the cotton fiber, it was washed with deionized water and dried to obtain ZIF-67 / cotton fiber; by repeating the above steps, different ZIF-67 loading amounts (ZIF-67) were obtained. n / cotton fiber; Step 2: Preparation of NiCoAl-LDH / cotton fiber: (ZIF-67) n / cotton fiber is immersed in an ethanol-water mixed solution of nickel nitrate hexahydrate and aluminum nitrate nonahydrate, placed in a reactor, and subjected to hydrothermal reaction. After the reaction is completed, the cotton fiber is cooled to room temperature, and the cotton fiber is taken out and dried to obtain NiCoAl-LDH / cotton fiber; Step 3: Preparation of polypyrrole / NiCoAl-LDH / cotton fiber: Pyrrole was dissolved in deionized water, NiCoAl-LDH / cotton fiber was placed in the solution, and magnetic stirring was performed in an ice-water bath; ferric chloride hexahydrate was dissolved in deionized water, and added dropwise to the pyrrole monomer solution, and reacted for a period of time at room temperature. After the cotton fiber was taken out, it was washed with hydrochloric acid and deionized water, and dried to obtain a polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material.
3. The method for preparing the hierarchical polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material according to claim 2, characterized in that: The following steps are involved: Step 1: (ZIF-67) n / Preparation of cotton fiber: Cobalt nitrate hexahydrate and 2-methylimidazole were dissolved in methanol solution, respectively, and cotton fibers of 10 cm × 10 cm were immersed in the methanol solution of 2-methylimidazole, to which the methanol solution of cobalt nitrate hexahydrate was slowly added, and aged at room temperature for 24 h. The cotton fibers were taken out and washed with deionized water for 2 to 3 times, and dried to obtain ZIF-67 / cotton fibers. By repeating the above steps, (ZIF-67) with different ZIF-67 loading amounts were obtained. n / cotton fiber; Step 2: Preparation of NiCoAl-LDH / cotton fiber: (ZIF-67) n / cotton fiber was immersed in an ethanol-water mixed solution of nickel nitrate hexahydrate and aluminum nitrate nonahydrate, placed in a reactor, and subjected to hydrothermal reaction at 90°C for 1 h. After the reaction was completed, the cotton fiber was cooled to room temperature, and the cotton fiber was taken out and dried to obtain NiCoAl-LDH / cotton fiber; Step 3: Preparation of polypyrrole / NiCoAl-LDH / cotton fiber: Pyrrole was dissolved in deionized water, and NiCoAl-LDH / cotton fiber was placed in the solution and magnetically stirred for 30 minutes in an ice-water bath. A certain amount of ferric chloride hexahydrate was dissolved in deionized water and added dropwise to the pyrrole monomer solution within 30 minutes. The mixture was reacted at room temperature for a period of time. The cotton fiber was taken out, washed with hydrochloric acid and deionized water, and dried to obtain a polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material.
4. The method for preparing the hierarchical polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material according to claim 3, characterized in that: The following steps are involved: Step 1: Preparation of (ZIF-67)4 / cotton fiber: 3.87 g of cobalt nitrate hexahydrate and 4 g of 2-methylimidazole were dissolved in 120 mL of methanol solution, and cotton fibers with a size of 10 cm × 10 cm were soaked in the methanol solution of 2-methylimidazole. The methanol solution of cobalt nitrate hexahydrate was slowly added thereto, and the fibers were aged at room temperature for 24 h. The cotton fibers were taken out and washed with deionized water, and dried at 50°C to obtain ZIF-67 / cotton fibers. The above steps were repeated 4 times to obtain (ZIF-67)4 / cotton fibers. Step 2: Preparation of NiCoAl-LDH / cotton fiber: Nickel nitrate hexahydrate and aluminum nitrate nonahydrate in a molar ratio of 0.5 to 4:1 were dissolved in 60 mL of an ethanol-water mixed solution, (ZIF-67)4 / cotton fiber was placed in the mixed solution, and hydrothermally reacted at 90°C for 1 h. After the reaction was completed, the cotton fiber was cooled to room temperature, washed with deionized water, and dried at 60°C to obtain NiCoAl-LDH / cotton fiber; Step 3: Preparation of polypyrrole / NiCoAl-LDH / cotton fiber: 0.2 M pyrrole was dissolved in deionized water, and NiCoAl-LDH / cotton fiber was placed in the solution and magnetically stirred for 30 min in an ice-water bath. Ferric chloride hexahydrate with a molar ratio of 4 times that of pyrrole was dissolved in deionized water and added dropwise to the pyrrole monomer solution within 30 min. The reaction was carried out in an ice-water bath for 120 min. The cotton fiber was taken out and washed with hydrochloric acid and deionized water, and dried at 60°C to obtain polypyrrole / NiCoAl-LDH / cotton fiber flexible electrode material.
Citation Information
Patent Citations
Array molybdenum-doped cobalt diselenide composite material and preparation method and application thereof
CN115249797A